Ação antibacteriana e antifúngica de nanopartículas de sílica funcionalizada contendo brometo de cetiltrimetilamônio (CTAB) - Mariano, Pedro Higor Rocha (2024)
The development of nanomaterials has enabled the improvement of problem-solving in various fields. In medicine, the use of drug nanocarriers has contributed to the development of new forms of disease treatment, such as cancer and fungal and bacterial infections, by employing lower drug concentrations, thereby reducing their side effects. Silica nanoparticles are nanoscale spheres containing siloxane, whose surface can be modified for transporting different drugs. The emergence of new bacterial and fungal strains resistant to standard treatments demands the development of new antimicrobial agents. In this study, the antibacterial and antifungal activity of cetyltrimethylammonium bromide in silica nanoparticles functionalized with amine groups (MPSi-CTAB) was evaluated. The material synthesis is a modification of the Stöber method, where tetraethoxysilane (TEOS) and 3-aminopropyltriethoxysilane (APTES) were used as silicon sources and CTAB as a structure modulator of the nanomaterial. After synthesis, extractions (partial and full) of CTAB were performed using a 1% HCl/Ethanol solution. The material was characterized by scanning and transmission electron microscopy (SEM and TEM respectively), Fourier-transform infrared spectroscopy (FTIR), 13C nuclear magnetic resonance (NMR 13C), thermogravimetry (TG) to estimate the amount of CTAB (CTAB, 9.4% w/w), and zeta potential (MPSi: +13 mV and MPSi-CTAB: +41 mV). Antibacterial and antifungal assays were conducted in 96-well plates, diluting MPSi, MPSi-CTAB, and antibiotics in antibacterial assays, using resazurin. To evaluate material toxicity, hemolytic action tests were conducted with MPSi-CTAB and cytotoxic tests with murine fibroblasts against MPSi and MPSi-CTAB, both serially diluted. The results showed that MPSi-CTAB exhibited antimicrobial activity against methicillin-resistant Staphylococcus aureus ATCC 700698 with MIC and MBC (minimum inhibitory concentration and minimum bactericidal concentration, respectively) of 0.625 mg m L-1 and 1.25 mg mL-1, respectively, The combination of MPSi-CTAB with ampicillin or tetracycline reduced MIC values by 32 and 16 times, respectively, besides inhibiting biofilm formation for the four strains studied (Staphylococcus aureus ATCC 25923 and Staphylococcus epidermidis ATCC 12228 and methicillin-resistant strains, Staphylococcus aureus ATCC 700698 and Staphylococcus epidermidis ATCC 35984). The developed material also exhibited antifungal activity against Candida strains with MIC values ranging from 0.0625 to 0.5 mg m L-1. MPSi-CTAB showed low cytotoxicity in murine fibroblasts, with over 80% of cells remaining viable with 0.31 mg m L-1 of the material. Finally, a gel formulation based on carbopol, triethanolamine, and MPSi-CTAB or MPSi was prepared, and growth inhibition assays in Petri dishes were evaluated. The antibacterial and antifungal action was compared to that of commercial products (ketoconazole-based antifungal and 70% w/w alcohol gel). It was also observed that MPSi showed no antibacterial, antifungal, biofilm formation inhibition, or significant cytotoxicity. These results demonstrate the potential of MPSi-CTAB material for further research aimed at developing treatments or prevention of infections caused by methicillin-resistant Staphylococcus species and Candida.